RTHP-10. PREDICTORS OF LINEAR ACCELERATOR VERSUS GAMMA KNIFE STEREOTACTIC RADIOSURGERY USE FOR BRAIN METASTASES IN THE UNITED STATES. (11th November 2019) - McClelland III, Shearwood; Degnin, Catherine; Chen, Yiyi; Watson, Gordon; Jaboin, Jerry
Abstract: INTRODUCTION: Stereotactic radiosurgery (SRS) for brain metastases is predominantly delivered via single-fraction Gamma Knife SRS (GKRS) or linear accelerator (LINAC) in 1–5 fractions. Predictors of SRS modality have been sparsely examined on a nationwide level. METHODS: The 2010–2016 National Cancer Database identified brain metastases patients from non-small cell lung cancer throughout the United States (US) having undergone SRS. A multivariable logistic regression model characterized SRS receipt, adjusting for patient age, dose, geographic location of treatment, facility type, and distance from treatment facility. RESULTS: A total of 1, 760 patients received GKRS, while 1, 064 patients received LINAC SRS. Treatment at non-academic facilities was associated with increased LINAC SRS receipt, most prominently in the Midwestern (OR= 6.23; p< 0.001), Northeastern (OR= 4.42; p< 0.001), and Southern US (OR= 1.96;p< 0.001). Administered doses of 18–19 Gy (OR= 1.42;p= 0.025), 20–21 Gy (OR= 1.82;p< 0.001), and 22–24 Gy (OR= 3.11;p< 0.001) were associated with increased LINAC SRS receipt, as was patient location within 20 miles of a radiation treatment facility (OR= 1.27;p= 0.007). CONCLUSIONS: Despite Gamma Knife being more prominently used over LINAC for SRS, patients treated at non-academic facilities outside of the Western US were substantially more likely to receive LINAC over Gamma Knife. Patients located in the Midwest were 523% more likely, Northeast 342% more likely, and South 96% more likely to receive LINAC when treated at a non-academic facility. Increasing dose independently predicted LINAC over GKRS, indicating that smaller tumors – particularly those less than two centimeters (consistent with RTOG 90-05 recommendations) – are being treated with LINAC. Finally, patients residing in close proximity to a treatment center were 27% more likely to receive LINAC, likely indicative of the increased geographic accessibility of LINAC compared with GKRS. These findings should result in hypothesis-generating questions to further explore predictors of LINAC versus GKRS.